Overview of Dengue Fever (DHF) Cases in East Java Province in 2022 - 2023 - Ramadhan Tosepu; Nirin Raudhatul Janna; Norma Ilham Siddik; Nurul Aina Jamil; Nisa Al Jannah Harsit; Pramudya Wira Ananta (Journal of Health Science and Pharmacy, 2026)
Background: Dengue hemorrhagic fever (DHF) remains an endemic vector-borne disease in Indonesia, characterized by substantial annual fluctuations and recurrent outbreaks, particularly during the rainy season. East Java Province continues to contribute a considerable burden of reported DHF cases, underscoring the need for epidemiological profiling to support targeted control efforts. Objective: This study aimed to describe the temporal and spatial distribution of DHF cases in East Java Province during 2018–2020 and to summarize case patterns according to selected demographic and contextual indicators. Methods: A quantitative descriptive study with a time-series approach was conducted using secondary data. DHF case data were obtained from the East Java Provincial Health Profile (2018–2020). Climate variables (air temperature, relative humidity, rainfall, and sunshine duration) and population density data were retrieved from the Central Statistics Agency for the same period. Data were analyzed descriptively to assess year-to-year changes and distributions by time and district/city, and stratified by sex where available. Results: The number of DHF cases in East Java showed an overall increase from 2018 to 2020, although the pattern was unstable across years and varied substantially between districts/cities. Higher case concentrations were observed in several areas, reflecting heterogeneous transmission dynamics potentially associated with population density and seasonal climatic conditions. Conclusion: DHF burden in East Java increased during 2018–2020 with pronounced spatiotemporal variation. These findings support strengthening routine surveillance, climate-informed early warning, and community-based vector control to enhance prevention and response. Keywords: dengue hemorrhagic fever; East Java; climate; population density; time series